PEDAGOGIC RESEARCH IN THE CONTEXT OF A DIALOGUE BETWEEN AUTHOR (RESEARCHER) AND SCIENTIFIC COMMUNITY - Kira A. Tret’Yakova; Andrey V. Korzhuev; Albina R. Sadykova (Высшее образование в России)
The article discusses philosophic representation of a research dialogue, typology of pedagogic dialogues. Dialogue is viewed as a method of scientific pedagogic discovery and as a form of multiaspect reflection by participants their ideas, approaches and positions and also as a form of scientific cooperation.